Prevalance of Burnout Syndrome Among Anaesthesia Residents in Tertiary Care Hospitals of Karachi - Ayesha Tahir, Khawar Aziz, Arif Iftikhar, Muhammad Sirajuddin, Ali Asghar, Laila Khalid (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study is to assess the incidence of burnout syndrome among Karachi’s anesthesiology residents in teaching hospitals. Methods: This cross-sectional research was undertaken at tertiary care hospitals of Karachi. Ethical committee permission, authorization from institutions, and agreement from residents were all required before data collection from 144 anesthesiology residents could begin. Participants were recruited from both public and private healthcare facilities. The demographic data from a questionnaire was used to determine the prevalence of the burnout syndrome, which is defined by feelings of emotional tiredness, depersonalization, and decreased personal accomplishment. SPSS was used to generate descriptive statistics. Results: The mean working hours of the participants in government and private hospitals were 64.21±12.40 and 90.24±25.01 hours. A significant difference (p=0.000) in the mean working hours of the participants were observed in participants at government and private hospitals. Emotional exhaustion score of the participants in government and private hospitals were 15.72±11.56 and 22.69±11.20. A significant difference (p=0.002) in the mean emotional exhaustion score of the participants were observed in participants at government and private hospitals. Depersonalization score of the participants in government and private hospitals were 8.79±6.71 and 12.82±7.59. A significant difference (p=0.004) in the mean depersonalization score of the participants were observed in participants at government and private hospitals. Reduced personal achievement score of the participants in government and private hospitals were 12.97±11.96 and 19±12.65. A significant difference (p=0.002) in the mean reduced personal achievement score of the participants were observed in participants at government and private hospitals. Conclusion: We observed the variation in burnout of private hospital versus government hospital. Residents working in private hospital work for extensive hours as compared to government hospital residents. There is an extensive need of comprehensive support groups, humane number of working hours, improved de-stressing activities for mental health of resident physicians and enhance their productivity. Keywords: Burnout, emotional exhaustion, depersonalization, Reduced personal achievement